3. MENJAMIN KETERSEDIAAN PANGAN : TUGAS BERAT BIROKRASI PEMERINTAH - Martini, Rina (Faculty of Social and Political Sciences Diponegoro University, 2009)
Indonesian society is now in a hard condition. One of the causes of this hardship is the rise of oil price which causes the ability of people to buy goods and services goes down sharply. Because of this matter, inflation cannot be avoided, as well as malnutrition, which threats the people, particularly who live in poverty. In relation to this, it is the government’s responsibility to tackle this problem. It is not an easy task since the government has to deal with some obstacles, including the narrow perception of food which is focused only on rice, the decreasing number of land area available for farming for the massive infrastructure building, the climate change, and the corrupt bureaucracy. If the government wants to overcome this problem, they have to think about the solution, involving all part of society in order to maintain the food availability.